2015
DOI: 10.1111/exd.12652
|View full text |Cite
|
Sign up to set email alerts
|

UV radiation induces CXCL5 expression in human skin

Abstract: CXCL5 has recently been identified as a mediator of UVB‐induced pain in rodents. To compare and to extend previous knowledge of cutaneous CXCL5 regulation, we performed a comprehensive study on the effects of UV radiation on CXCL5 regulation in human skin. Our results show a dose‐dependent increase in CXCL5 protein in human skin after UV radiation. CXCL5 can be released by different cell types in the skin. We presumed that, in addition to immune cells, non‐immune skin cells also contribute to UV‐induced increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Although some studies have demonstrated that UV irradiation induces distinct chemokines, such as CCL3, CCL20, CXCL1, CXCL2, CXCL3 and CXCL5 in human skin, these studies did not examine the expression or function of chemokines in isolated human SC fat tissues. CXCL5 is a proinflammatory chemokine that is linked to adipose tissue inflammation and insulin resistance, which antagonizes insulin signalling via the JAK‐STAT pathway .…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have demonstrated that UV irradiation induces distinct chemokines, such as CCL3, CCL20, CXCL1, CXCL2, CXCL3 and CXCL5 in human skin, these studies did not examine the expression or function of chemokines in isolated human SC fat tissues. CXCL5 is a proinflammatory chemokine that is linked to adipose tissue inflammation and insulin resistance, which antagonizes insulin signalling via the JAK‐STAT pathway .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of significant associations with monthly sun hours could be attributed to a number of factors. Although UV-radiation have previously been shown to directly affect the circulating levels of plasma proteins (Vostalova et al, 2013, Reichert et al, 2015), the sun hours are likely to be viewed as a proxy variable to other seasonal changes such as blooming or pollen levels which in turn triggers the immune system, or various forms of changes in lifestyle such as seasonal intakes of food and changes in habits of physical activity. The number of sun-hours per month available from the SMIHI is also an average over the past 30 years and the actual sun-hours at the individual sampling dates could differ from the used number.…”
Section: Discussionmentioning
confidence: 99%
“…UV-radiation causes inflammatory responses in the skin and several cytokines are affected by UV-radiation. Specifically, production of C-X-C motif chemokine ligand 5 (CXCL5) have been shown to be up-regulated in human skin (Reichert et al, 2015) in response to UV-radiation and changes in plasma levels of several interleukins have been shown in vivo in mouse models (Vostalova et al, 2013), suggesting that seasonal variation is likely to be measurable in human plasma. In order to investigate the effect of storage time in freezer, chronologic age at sampling, sampling month, and season (sunlight), we determined the abundance level of 122 plasma proteins using the Protein Extension Assay (PEA) in 106 women sampled at 380 occasions spanning from 1988 to 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of UVR on the skin include reddening, sunburn and tanning, vitamin D synthesis and the development of skin cancers, all of which may involve skin MCs. At the cellular level, exposure of the skin to UVR also results in a large and diverse set of responses of cutaneous cells such as proliferation, differentiation, apoptosis, the release of mediators, and the expression of miRNA profiles . Skin MCs may be affected by these effects of UVR directly and indirectly, and they may be involved as intermediaries of UVR effects on other skin cells.…”
Section: Why We Should Care About How Mast Cells Respond To Ultraviolmentioning
confidence: 99%